IMPLEMENTATION OF EXPONENTIAL SMOOTHING METHOD IN THE NUMBER OF DIVORCE RATE IN INDONESIA - Yuliani, Eva; Rakhmawati, Fibri; Husein, Ismail (Journal of Mathematics and Scientific Computing With Applications, 2022)
The divorce rate in Indonesia from 2007 to 2020 has increased. The increase in the divorce rate in Indonesia has an impact on the mental condition of children. The purpose of this study is to find out the results of the number of divorce rates in Indonesia in 2021-2022 and to see which accuracy is more accurate between the Double Exponential Smoothing Method and the Triple Exponential Smoothing Method. Comparison between the Double Exponential Smoothing Method and the Triple Exponential Smoothing Method which has more accurate forecasting, namely the Double Exponential Smoothing Method with parameter values and the MAPE value of 14.27%, the equation for forecasting the divorce rate in Indonesia is . The results of the study show that the divorce rate in Indonesia will increase in 2021 with 285,903 cases and decrease in 2022 with 268,649 cases.